Macroeconomic Stability and Sustainable Growth in Pakistan: ARDL Evidence on the Role of Energy, Inflation, and Foreign Investment - Bin Jawaid, Zaid; Abrar, Nabiha; Ahsan, Aitzaz; Siraj, Khursheed Uddin (International Journal of Energy Economics and Policy, 2025)
This study investigates the determinants of macroeconomic stability and sustainable growth in Pakistan using an Autoregressive Distributed Lag (ARDL) bounds testing approach. Drawing on annual data spanning 1970 to 2023, the analysis explores the dynamic interactions among GDP growth, money supply, fuel imports, foreign direct investment, oil prices, and inflation. The ARDL bounds test confirms a long-run cointegrating relationship among these macroeconomic variables, indicating that they move together over time. Long-run estimates suggest that increases in money supply and fuel imports are associated with higher GDP growth. At the same time, elevated inflation and foreign direct investment significantly negatively impact economic performance. Foreign direct investment shows strong positive effects in the short term. However, inflation and lag-fueled imports have more complicated impacts on GDP growth, which are reflected as delayed negative influences. Diagnostic tests for autocorrelation and heteroskedasticity support the model's accuracy, and the mistake correction mechanism points to a rapid adjustment process with deviations from the long-run equilibrium being corrected at an annual rate surpassing 130%. These findings emphasize the need for stabilizing inflation, ideal foreign investment policies, and different energy sources to produce resilient macroeconomic stability and sustainable economic growth in Pakistan.